Handoff performance analysis for multihoming-based network mobility scheme - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Hasan, Mohammad Kamrul (Science and Engineering Research Support Society, 2016)
The necessity for multihoming functionality emerged since the standard Network Mobility Basic Support Protocol (NEMO BSP) acquiesces the Mobile Router (MR) to bind single Care of Address (CoA) at once with its Home Agent (HA) only. Besides, NEMO networks are usually attached through the wireless which results in less stable links. There could also be several Mobile Network Nodes (MNNs) behind the MR. Thus, a loss of Internet connectivity has higher impact compared to a single MNN. To ensure a continuous Internet connectivity to mobile networks, it is preferable to use multihoming mechanism in which MR is equipped with multiple interfaces as well as technologies. This paper has proposed a multihoming-based scheme on Proxy MIP6 (PMIPv6) domain for handoff performance analysis relating to handoff delay, packet delivery ratio, as well as throughput at different number of MR, speed and time. After that, it has developed a simulation model to assess the proposed scheme as well as compared it with Network Mobility Basic Support Protocol (NEMO BSP) and multi-interfaced scheme. Results attained from evaluation will support the network engineer to pick a suitable multihoming-based scheme in mobile environment at different number of MR, speed and time.